PKM Pelatihan dan Pendampingan Literasi (Baca Tulis) untuk Meningkatkan Mutu Pendidikan bagi Siswa MI Tarbiyatul Islam - Feriska Listrianti; Rizki Sandi Kurniawan; M. Alfin Fauzi; Selvi Ika Damayanti (Universitas Nurul Jadid, 2022)
Education 4.0 does not only focus on the use of technology, but students' reading interest also needs to be improved to meet Education 4.0. The rapid flow of information and technology in the 4.0 education era has an impact on the limited time that students have to read. In fact, students' literacy skills in reading and writing can certainly be indispensable for students to keep abreast of all developments, especially those related to their education. Reading is one of the important things in all kinds of learning processes. Through reading various sciences, which can lead to success, we can get. This article aims to describe the implementation of the reading literacy movement for elementary school students at MI Tarbiyatul Islam Kandang Jati Kulon. From the initial observations, it was shown that the teachers at the school were still passive in carrying out the reading and writing literacy movement. The teachers at Madrasah Ibtidaiyah (MI) have not actively paid attention to efforts to increase students' reading literacy. Through various fun activities for students, and trying to foster a love of reading and writing in students through the application of reading and writing literacy movements. Proven enthusiasm in participating in the training from beginning to end, the results of this training and mentoring show that through fun activities as an effort to implement the reading literacy movement, students become more enthusiastic and enthusiastic to increase interest in reading.